Proceedings of the International Conferences on Educational, Social Sciences and Technology - ICESST 2018 2018
DOI: 10.29210/2018125
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the current account balance in Indonesia

Abstract: The open economic system adopted by Indonesia disrupts the current account balance. This study aims to analyze and explained the causality of the current account balance with macroeconomic variables using the VAR (Vector Autoregression) approach. The data in this study used time series from 2005 quarter 1 to 2015 quarter 4. The results showed that macroeconomic variables have no causality relationship with current account balance in Indonesia. The research recommended to the financial policy authority relates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The condition of the current account balance often fluctuates due to imbalances in exports and imports [4]- [6]. International trade can result in a country more likely to export which results in a surplus or more tend to import resulting in a deficit.…”
Section: Rd Ircebmentioning
confidence: 99%
“…The condition of the current account balance often fluctuates due to imbalances in exports and imports [4]- [6]. International trade can result in a country more likely to export which results in a surplus or more tend to import resulting in a deficit.…”
Section: Rd Ircebmentioning
confidence: 99%
“…Kovacevic (2017) observed that exchange rate, inflows of foreign direct investment, and foreign remittances are creating imbalances in this account in 9 SEE countries. For Malaysia, these reasons were discovered to be the growth in real GDP and the value of money (Kurniadi and Aimon, 2018). Riaz, Javid, and Mubarik (2019) investigated this issue for South Asian Economies and concluded that domestic income and foreign assets play a crucial role in this regard.…”
Section: Graph 1: Cad As % Of Gdpmentioning
confidence: 99%
“…Apart from the monetary policies carried out by each country, fluctuating current account conditions are also inseparable from shocks to macroeconomic variables [10].…”
Section: Introductionmentioning
confidence: 99%